Value creation by Indian companies: A comparative study over two time periods - JHUNJHUNWALA, Aditya; CHAUDHURI, Tamal D.; BHAMRAH, Gulshan K. (Turkish Economic Review, 2019)
Abstract. The objective of this paper is to derive economic profit generated by Indian companies over two time periods and see whether there has been any fundamental change in the performance of companies and the sectors within which they belong. We focus on non-finance companies. The purpose is two-fold. First, to get an idea about how Indian companies have fared over the two time periods and whether there has been any structural change. Second, to help companies decide on their next strategic move and allocate funds for the purpose. The study also focusses on the relationship between size and economic profit, where invested capital and market capitalization represents size. The methodology presented in the paper enables us to understand the performance of Indian companies and also the sectors within which they belong. Keywords. Economic profit, Invested capital, Quintile distribution, Market capitalization, Sector. JEL. G11, G14, G32, L25, E22.